A T-Cell Surface Marker Panel Predicts Murine Acute Graft-Versus-Host Disease - Bäuerlein, Carina A.; Qureischi, Musga; Mokhtari, Zeinab; Tabares, Paula; Brede, Christian; Jordán Garrote, Ana-Laura; Riedel, Simone S.; Chopra, Martin; Reu, Simone; Mottok, Anja; Arellano-Viera, Estibaliz; Graf, Carolin; et al. (Frontiers in Immunology, 2021)
Acute graft-versus-host disease (aGvHD) is a severe and often life-threatening complication of allogeneic hematopoietic cell transplantation (allo-HCT). AGvHD is mediated by alloreactive donor T-cells targeting predominantly the gastrointestinal tract, liver, and skin. Recent work in mice and patients undergoing allo-HCT showed that alloreactive T-cells can be identified by the expression of α4β7 integrin on T-cells even before manifestation of an aGvHD. Here we investigated whether the detection of a combination of the expression of T-cell surface markers on peripheral blood (PB) CD8+ T-cells would improve the ability to predict aGvHD. To this end we employed two independent preclinical models of minor histocompatibility antigen mismatched allo-HCT following myeloablative conditioning. Expression profiles of integrins, selectins, chemokine receptors and activation markers of PB donor T-cells were measured with multiparameter flow cytometry at multiple time points before the onset of clinical aGvHD symptoms. In both allo-HCT models we demonstrated a significant upregulation of α4β7 integrin, CD162E, CD162P and conversely, a downregulation of CD62L on donor T-cells which could be correlated with the development of aGvHD. Other surface markers, such as CD25, CD69 and CC-chemokine receptors were not found to be predictive markers. Based on these preclinical data from mouse models we propose a surface marker panel on peripheral blood T-cells after allo-HCT combining α4β7 integrin with CD62L, CD162E and CD162P (cutaneous lymphocyte antigens, CLA, in humans) to identify patients at risk for developing aGvHD early after allo-HCT.